2006
DOI: 10.1091/mbc.e05-12-1112
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of the Golgi Apparatus for Cargo Transport Prior to Complete Assembly

Abstract: In yeast, particular emphasis has been given to endoplasmic reticulum (ER)-derived, cisternal maturation models of Golgi assembly while in mammalian cells more emphasis has been given to golgins as a potentially stable assembly framework. In the case of de novo Golgi formation from the ER after brefeldin A/H89 washout in HeLa cells, we found that scattered, golgin-enriched, structures formed early and contained golgins including giantin, ranging across the entire cis to trans spectrum of the Golgi apparatus. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 45 publications
8
28
0
Order By: Relevance
“…Next, we compared the distribution of GM130 with that of Bap31 during recovery from BFA treatment. GM130 is one of the fast-moving proteins during BFA recovery (Jiang et al, 2006). As reported previously (Nakamura et al, 1995;Seemann et al, 2000;Ward et al, 2001), GM130 was distributed in punctate structures in BFA-treated cells (Supplemental Figure S3, second row).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Next, we compared the distribution of GM130 with that of Bap31 during recovery from BFA treatment. GM130 is one of the fast-moving proteins during BFA recovery (Jiang et al, 2006). As reported previously (Nakamura et al, 1995;Seemann et al, 2000;Ward et al, 2001), GM130 was distributed in punctate structures in BFA-treated cells (Supplemental Figure S3, second row).…”
supporting
confidence: 81%
“…As reported previously (Nakamura et al, 1995;Seemann et al, 2000;Ward et al, 2001), GM130 was distributed in punctate structures in BFA-treated cells (Supplemental Figure S3, second row). Although previous studies showed that combined treatment of normal rat kidney or HeLa cells with BFA followed by BFA plus H89 causes ER localization of GM130 (Puri and Linstedt, 2003;Jiang et al, 2006), such redistribution was not observed in COS-7 cells when 50 M H89 in addition to 10 M BFA was used (data not shown). This is perhaps due to a relatively weak action of H89 on COS-7 cells, as described above.…”
Section: Bap31 Movement and Golgi Reassembly Occur Independently Durimentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, removal of microtubules does not prevent retrograde transport of Golgi proteins to the ER. This was well demonstrated by preventing ER export (using BFA or H89, or dominant-negative Sar1) at the same time as microtubule disruption (Jiang et al, 2006;Puri and Linstedt, 2003;Storrie et al, 1998). In our study, inhibiting new synthesis of proteins did not prevent functional maturation of Golgi elements.…”
Section: Functional Maturation Of Golgi Mini-stackssupporting
confidence: 56%
“…• C in the presence of cycloheximide to chase newly synthesized tsO45G into the Golgi apparatus and plasma membrane (23,49). Following deconvolution with HUYGENS PROFESSIONAL software (Scientific Volume Imaging), tsO45G-GFP distribution patterns were scored visually as previously described (31).…”
Section: Microinjectionmentioning
confidence: 99%